If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + 15y + 5 = 0 Reorder the terms: 5 + 6x + 15y = 0 Solving 5 + 6x + 15y = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + 6x + -5 + 15y = 0 + -5 Reorder the terms: 5 + -5 + 6x + 15y = 0 + -5 Combine like terms: 5 + -5 = 0 0 + 6x + 15y = 0 + -5 6x + 15y = 0 + -5 Combine like terms: 0 + -5 = -5 6x + 15y = -5 Add '-15y' to each side of the equation. 6x + 15y + -15y = -5 + -15y Combine like terms: 15y + -15y = 0 6x + 0 = -5 + -15y 6x = -5 + -15y Divide each side by '6'. x = -0.8333333333 + -2.5y Simplifying x = -0.8333333333 + -2.5y
| O(10)O(n)=2n-1 | | 6p+6+1=13 | | 2(b-1)=5b+1 | | 2(6x+3)=2(x+6) | | 9/0= | | 12y-4y=-128 | | -4=5n-n | | 8x+4=196 | | 4x+8=196 | | 30t+2.50=67.50 | | -92=-2-5(-2+4b) | | 1.64=x-45 | | 3/5x(-5/8)= | | 2*x^3-6*x+2=0 | | (11+a)+16= | | 4x-x+x=2+10 | | 3x-5=10x-56 | | 2(6x-6)=6(5x-5) | | 4a-2(a-5)=-2 | | 6t+t+40=180 | | b+75+2b=180 | | .5x^3-3x^2+1=0 | | 5m-7m+18=10 | | 3*log(x-1)=9 | | 0.7x-3.5=0.6-x | | (5a-2b)x(5a-2b)= | | 3x+19-6x=10 | | 6=c-15 | | 9(6k+9)+10(7k+7)= | | 10-5x=3x-22 | | 630/189 | | 4/5•(-2/9) |